Preparation of SiC/Al2O3 composite materials from coal fly ash - LI Zi-yong; WU Chun-han; YU Qing-chun; ZHOU Yue-zhen; LI Wei; YANG Bin (工程科学学报)
By using coal fly ash as a raw material and graphite as a reducer in the protective atmosphere of argon,SiC/Al2O3 composite materials were synthesized by carbothermal reduction.The reaction process of reduction of the coal fly ash was studied,and its influencing factors were investigated.The composition of products obtained at different temperatures was analyzed by X-ray diffraction,and the microstructure was observed by scanning electron microscopy and energy dispersive spectroscopy.The results show that the phases of quartz and mullite in the coal fly ash are almost completely reactive at 1673 and 1773 K,respectively.With increasing temperature,the contents of SiC and Al2O3 increase,and the suitable temperature condition is 1773 to 1873 K.The extension of holding time is good for the formation of SiC and Al2O3,and the appropriate holding time is 3 to 4 h.Increasing the carbon content has positive effect on the formation of SiC and Al2O3,and the optimum molar ratio of C/Si is 4 to 5.In the prepared SiC/Al2O3 composite materials,SiC is homogeneously dispersed in the products,and its granularity is less than 20 μm.